Allostatic load and progression of cardio-renal multimorbidity: A UK biobank study - Qianshen Zhu; Lingling Xu; Zhixing Fan; Hongbo Li (PLoS ONE, 2026)
Background Cardio-renal multimorbidity (CRM), the coexistence of cardiovascular disease (CVD) and chronic kidney disease (CKD), imposes a significant healthcare burden. Allostatic load (AL), indicating cumulative physiological dysregulation from chronic stress, may be a modifiable risk factor for CRM. Methods This study included 396,927 participants with a median follow-up of 13.67 years. AL was assessed via 10 biomarkers. Multistate models were used to analyze transitions from health to first cardio-renal disease (FCRD), to CRM, and to death. Results Higher AL was significantly associated with increased risks of progression from health to FCRD, to CRM, and to death. The transition from FCRD to CRM was most affected by high AL. AL also had a stronger association with the transition from health to CKD than to CVD. Stratified analyses showed more pronounced associations in younger participants, those with higher socioeconomic status (SES), and unhealthy diets. Conclusion AL is a significant upstream factor in CRM development and progression. Early identification of individuals with high AL could aid in risk assessment and prevention strategies for CRM.